2011
DOI: 10.1016/j.vaccine.2011.01.067
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ support for voluntary provision of HPV vaccine in schools

Abstract: HPV vaccination rates among adolescents in the United States lag behind some other developed countries, many of which routinely offer the vaccine in schools. We sought to assess mothers’ willingness to have their adolescent daughters receive HPV vaccine at school. A national sample of mothers of adolescent females ages 11–14 completed our internet survey (response rate = 66%). The final sample (n = 496) excluded mothers who did not intend to have their daughters receive HPV vaccine in the next year. Overall, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 20 publications
(25 reference statements)
8
23
0
Order By: Relevance
“…Taken together with other research on acceptability of delivering adolescent vaccines outside the medical home, 16,17,21,28 the moderate levels of comfort among parents and sons in our study are promising for expanding vaccine coverage in the US and hopefully increasing coverage rates to match those of other countries (e.g., Australia and the UK) that already offer the vaccine non-traditional settings. Indeed, comfort with these settings may be higher as such programs become more common.…”
Section: Potential Conflicts Of Interestsupporting
confidence: 60%
See 3 more Smart Citations
“…Taken together with other research on acceptability of delivering adolescent vaccines outside the medical home, 16,17,21,28 the moderate levels of comfort among parents and sons in our study are promising for expanding vaccine coverage in the US and hopefully increasing coverage rates to match those of other countries (e.g., Australia and the UK) that already offer the vaccine non-traditional settings. Indeed, comfort with these settings may be higher as such programs become more common.…”
Section: Potential Conflicts Of Interestsupporting
confidence: 60%
“…Efforts to maximize HPV vaccine delivery in alternative settings will also need to address multiple policy and logistical concerns that are beyond the scope of the current study, such as coordinating medical/vaccination records with the medical home, billing insurance and obtaining parental consent where necessary. 13,14,16,19,21,28 Additional research is needed to identify strategies to increase acceptability, evaluate the feasibility of wide-scale implementation of vaccination located in alternative settings, and explore ways to ensure continuity of care with the medical home.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 A national internet-based survey found that 67% of mothers were willing to vaccinate their children in school. 34 In this survey, parents who had not yet initiated vaccination demonstrated the highest intent to utilize school-located immunization programs. Similarly, we found that the majority of parents and providers supported school-located provision of HPV vaccination, and that intended program utilization was highest among parents whose daughters had not completed the vaccine series.…”
Section: Supporting School-entry Requirementsmentioning
confidence: 95%